Analisis Isi Video Channel Youtube Timothy Ronald Dalam Konten “Perang Dalam Pikiran” - Arfian Suryasuciramdhan; Risma Yanti; Reva Fisalsabila; Yusep Irsyad Najib Setiawan (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Excessive thinking is often experienced from adolescence to adulthood. The term that is better known in English is overthingking. Overthinking is a behavior of thinking about something excessively. This habit can make a person reflect too much on what has happened in the past, worry about the future, and think about things that will not necessarily happen. This excessive thinking often occurs when we are experiencing a problem, and are doubtful about what we have done. There are several ways to overcome overthinking itself, one of which is by using Mindfulness Therapy. War in the mind can be interpreted as a condition of someone who thinks about conditions without finding a result that will take action. War in the mind is also known as overthinking, namely overthinking over and over again thinking about things that can take up a lot of time. The aim of this research is to present a complete picture of content. This research explains the content/message of a piece of content. Overthinking has a negative influence on a person's thinking. To fight in one's mind means to speak against oneself, and purely from one's thoughts.